Perception of Farmers about Usefulness of University Kisan Mela - M. N. Ansari, A K Paswan, (Indian Journal of Extension Education, 2018)
The study was undertaken to know the perception of farmers about usefulness of university Kisan Mela. The study was conducted at Rajendra Agricultural University, Bihar where Kisan Mela was organized for three days from 5-7th March 2016, involving 120 randomly selected participating farmers. The findings indicated that maximum numbers of participants were middle age group, had matriculation level of education, belong to OBC category, untrained with small land holding and agriculture and subsidiary was major occupation. Good majority of participating farmers perceived that information received at Kisan Mela on Agricultural implements & machine, IFS, Dairy & AH, Mushroom Cultivation and Medicinal & Herbal planting were more useful. It was also observed that more than fifty percent of the respondents expressed their opinion that suggestions by experts, Kisan Gosthi and horticultural exhibition were very good. Most of them were of the opinion that sale of inputs, transport arrangement and food facilities in farmers fair were average.